Flexible relations, frail contacts and failing demands: How community groups and local institutions interact in local governance in the Netherlands. (December 2014) - de Wilde, Mandy; Hurenkamp, Menno; Tonkens, Evelien
This paper explores the way community groups, central to new systems of local governance, are related to local institutions and how those relations influence them. We draw from two theoretical approaches – behavioural and institutional – that offer different answers to the question: what makes community groups thrive? Based on an analysis of 386 community groups in the Netherlands, we distinguish four types of groups: feather light, cooperative, networked and nested groups. Then, in a neighbourhood case study we focus on the relations between groups and local institutions to gain a deeper insight into the institutional dynamics of urban governance. Moreover, we combine the findings of both studies claiming that different groups need different things from local institutions, and that in the current NPM-driven world only the higher educated community groups have productive relationships with local institutions, while others are somewhere in between frail contacts and failing demands.